THU0588-HPR Associations between Objective and Self-Reported Physical Activity Data in Rheumatoid Arthritis Patients. (10th June 2014) - Yu, C.-A.; Rouse, P.; Veldhuijzen van Zanten, J.; Metsios, G.; Ntoumanis, N.; Kitas, G.; Duda, J.
Abstract : Background: Rheumatoid arthritis (RA) patients suffer from periodic flare-ups causing joint swelling, pain and potential bone destruction. In addition, RA patient are at greater risk of cardiovascular disease. Therefore, physical activity (PA) has been identified as an important component of a holistic treatment programme [1]. However, research suggests that RA patients fail to reach the recommended PA levels to gain the associated benefits [2]. PA is typically assessed in the exercise literature with self-report measures or via accelerometery. To our knowledge, little is known about the associations between self-reported and objective PA measures in RA patients. Objectives: To describe and compare the self-reported and objectively measured physical activity profiles of RA patients. Secondly, to investigate the associations between self-reported and objectively measured PA levels in RA patients. Methods: 68 participants (42 female, 4 missing) wore an accelerometer (Actigraph) for an average of 6±1 days. The International Physical Activity Questionnaire (IPAQ) was also completed in reference to the same targeted time period. The associations between objective/self-reported PA levels were examined on sedentary time/total sitting time, light PA/walking, and moderate, vigorous PA and moderate-to-vigorous PA (MVPA) from both meassurements. Results: Self-reported time spent sitting (M=343±141 minutes) was significantly less than objectively measured sedentary time (M=583±98; t=-13.12, p<0.01). Participants reported significantly more moderate intensity PA behaviour (M=86±83 minutes) than was objectively recorded (M=19±17 minutes; t=6.65, p<0.01), and more vigorous PA (M=10±37 minutes) than that revealed via accelerometry (M≤1 minute; t=2.14, p<0.01). Objective sedentary time was positively correlated with self-reported levels of sitting (r=0.29, p<0.05). Objective light PA was positively associated with self-reported MVPA (r=0.27, p<0.05). Objective moderate PA was also positively correlated to subjective walking time (r=0.28, p<0.05) and reported moderate PA (r=0.30, p<0.05). Conclusions: Patients with RA reported engagement in significantly less sedentary time and significantly more physical activity than was objectively revealed via accelerometry. Despite the over-estimation of subjective PA and under-estimation of obejctive sedentary behaviour, the observed moderate significant associations provide some evidence of convergent validity for the IPAQ echoing findings from previous research [3]. The significant moderate correlation between self-reported MVPA and objective light PA suggests that RA patients may perceive PA to require more exertion. Therefore, the PA intensity guidelines may need to be re-considered for RA patients. References: Feinglass J, Thompson JA, et al. Effect of physical activity on functional status among older middle-age adults with arthritis. Arthritis & Rheumatism 2005;53(6):879-885. Fontaine KR, Heo M, & Bathon J. Are US adults with arthritis meeting public health recommendations for physical activity? Arthritism & Rheumatis 2004;50(2):624-628. Boon RM, Hamlin MJ, Steel GD, & Ross JJ. Validation of the New Zealand Physical Activity Questionnaire (NZPAQ-LF) and the International Physical Activity Questionnaire (IPAQ-LF) with accelerometry. British Journal of Sports Medicine 2008;44(10):741-746 Acknowledgements: Medical Research Council and NPRI. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5529